Effects of neuropsychiatric symptoms of dementia on reductions in activities of daily living in patients with Alzheimer's disease. Issue 6 (31st March 2020) - Okabe, Kiwamu; Nagata, Tomoyuki; Shinagawa, Shunichiro; Inamura, Keisuke; Tagai, Kenji; Nukariya, Kazutaka; Shigeta, Masahiro
Abstract : Aim: In patients with Alzheimer's disease (AD), cognitive impairments cause a progressive reduction in Activities of Daily Living (ADL). Neuropsychiatric symptoms (NPS) also appear in most patients; however, the association between NPS and reductions in ADL remains unclear. The present study evaluated whether NPS influence such reductions using two different ADL measures in patients with AD. Methods: Among 546 consecutive outpatients who visited the memory clinic at the Jikei University Kashiwa Hospital, we recruited 208 patients with AD and investigated the correlations between either the Physical Self‐Maintenance Scale (PSMS) score or the Instrumental ADL (IADL) level, and each of the Behavioral Pathology in AD (Behave‐AD) subscales. To clarify the causal relationships of these correlations, we then verified the associations between statistically significant demographic variables and the Behave‐AD subscales as well as the two ADL scales (PSMS score and IADL percentage) using a general linear model. Results: Neither the PSMS nor the IADL results were significantly influenced by the aberrant motor behaviors score. However, the IADL was significantly influenced by the Mini‐Mental State Exam (MMSE) score. Furthermore, diurnal rhythm disturbances and the interaction between diurnal rhythm disturbances score and the MMSE score significantly influenced the PSMS results. Conclusion: Basic ADL reductions may be influenced by diurnal rhythm disturbances, in addition to cognitive impairments in patients with AD. Furthermore, the interaction between the diurnal rhythm disturbances score and cognitive function may also influence basic ADL. Geriatr Gerontol Int 2020; : – .